2012
DOI: 10.1093/infdis/jis284
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Anelloviruses in Vitreous Fluid of Children With Seasonal Hyperacute Panuveitis

Abstract: Seasonal hyperacute panuveitis (SHAPU) is a potentially blinding ocular disease occurring in Nepal that principally affects young children. Random amplification of partially purified vitreous fluid (VF)-derived nucleic acid revealed the presence of human anelloviruses in VF of SHAPU patients. In a comparative study of patients with different ocular pathologies, SHAPU patients were at highest risk of harboring anelloviruses in their eyes. The majority of SHAPU patients had multiple anelloviruses in their VF. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 45 publications
0
21
1
1
Order By: Relevance
“…In two previous survey studies, TTV was isolated from the tears of 59% 34 and 66% 35 of subjects. Recently Smits et al 36 described recovery of TTV from the vitreous of children affected seasonal hyperacute panuveitis (SHAPU), a severe form of panuveitis that resembles endophthalmitis, which is endemic to Nepal. 37 The authors reported that TTV was found in~90% of vitreous samples from SHAPU patients, as well as ~50% of endophthalmitis samples, but not in vitreous samples recovered from retinal detachment surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In two previous survey studies, TTV was isolated from the tears of 59% 34 and 66% 35 of subjects. Recently Smits et al 36 described recovery of TTV from the vitreous of children affected seasonal hyperacute panuveitis (SHAPU), a severe form of panuveitis that resembles endophthalmitis, which is endemic to Nepal. 37 The authors reported that TTV was found in~90% of vitreous samples from SHAPU patients, as well as ~50% of endophthalmitis samples, but not in vitreous samples recovered from retinal detachment surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, bacterial growth (mainly Streptococcus pneumoniae) has been found in the vitreous culture of some affected eyes and Anello viruses have been isolated from vitreous of many eyes. 28,29 In pediatrics, the commonest identified cause was either JRA or Toxoplasmosis in previous studies. 30,31 But in this study, SHAPU was the commonest cause.…”
Section: Pattern Of Uveitis and Scleritis In Nepalmentioning
confidence: 97%
“…It has been described previously in Nepal and most often affects young, healthy children 29 . The etiology remains unclear, although a viral cause has been proposed 29,30 . Epidemics appear to follow a 2 year cycle and an association with white Tussock moths has been postulated.…”
Section: Seasonal Hyperacute Panuveitismentioning
confidence: 84%
“…Epidemics appear to follow a 2 year cycle and an association with white Tussock moths has been postulated. 29,31 …”
Section: Seasonal Hyperacute Panuveitismentioning
confidence: 99%
See 1 more Smart Citation